2006
DOI: 10.1158/0008-5472.can-05-2908
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Murine Retroviral Mutagenesis for Identification of Disease Genes in Human Acute Myeloid Leukemia

Abstract: Retroviral insertion mutagenesis is considered a powerful tool to identify cancer genes in mice, but its significance for human cancer has remained elusive. Moreover, it has recently been debated whether common virus integrations are always a hallmark of tumor cells and contribute to the oncogenic process. Acute myeloid leukemia (AML) is a heterogeneous disease with a variable response to treatment. Recurrent cytogenetic defects and acquired mutations in regulatory genes are associated with AML subtypes and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…It has been previously shown that mouse leukemia genes identified by retroviral insertion mutagenesis are more frequently differentially expressed in human acute leukemia than randomly selected genes or genes located more distantly from a provirus integration. 27,28 Interestingly, several genes flanking the integration sites, such as SOCS1, JARID2, PTPRE, HSP90, GADD45, MGAT5, PP2R5C or MN1, have been previously linked to carcinogenesis (Table 1). [29][30][31][32][33] The integration near the MN1 locus resulted in significantly increased levels of mRNA expression (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that mouse leukemia genes identified by retroviral insertion mutagenesis are more frequently differentially expressed in human acute leukemia than randomly selected genes or genes located more distantly from a provirus integration. 27,28 Interestingly, several genes flanking the integration sites, such as SOCS1, JARID2, PTPRE, HSP90, GADD45, MGAT5, PP2R5C or MN1, have been previously linked to carcinogenesis (Table 1). [29][30][31][32][33] The integration near the MN1 locus resulted in significantly increased levels of mRNA expression (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, similar findings were made with retrovirally marked human cells observed in the nondiabetic obese (NOD)/SCID xenotransplant setting, 46 whereas insertion sites observed in murine tumors induced by RCR rather overlap with the transcriptome of human leukemias. 52 We would therefore assume that all vectors that show an insertion bias for expressed genes and contain strong enhancer sequences raise the probability of inducing clonal dominance by insertional mutagenesis. This also implies that the risk of clonal dominance or even malignant transformation should be much lower if gene transfer occurs in cells that have partially or completely silenced the self-renewal program.…”
Section: Discussionmentioning
confidence: 99%
“…Heat maps demonstrating patterns of expression for many of these annotated genes are presented as Figures S1-S3, available on the Blood website (see the Supplemental Materials link at the top of the online article). A number of genes previously associated with AML pathogenesis [23][24][25] were also developmentally regulated during myeloid maturation ( Figure S4; Table S1). …”
Section: Dysregulated Gene Expression In Apl 963mentioning
confidence: 93%